miR-31 from Mesenchymal Stem Cell-Derived Extracellular Vesicles Alleviates Intervertebral Disc Degeneration by Inhibiting NFAT5 and Upregulating the Wnt/β-Catenin Pathway - Baodong Wang; Na Xu; Li Cao; Xiaojun Yu; Shanxi Wang; Qikun Liu; Yinguang Wang; Haoran Xu; Yang Cao (Stem Cells International)
In this study, we explored the regulatory mechanism of intervertebral disc degeneration (IDD) that involves miR-31 shuttled by bone marrow mesenchymal stem cell-derived extracellular vesicles (BMSC-EVs) and its downstream signaling molecules. Nucleus pulposus cells (NPCs) were isolated and treated with TNF-α to simulate IDD in vitro. The TNF-α-exposed NPCs were then cocultured with hBMSCs or hBMSC-EVs in vitro to detect the effects of hBMSC-EVs on NPC viability, apoptosis, and ECM degradation. Binding between miR-31 and NFAT5 was determined. A mouse model of IDD was prepared by vertebral disc puncture and injected with EVs from hBMSCs with miR-31 knockdown to discern the function of miR-31 in vivo. The results demonstrated that hBMSC-EVs delivered miR-31 into NPCs. hBMSC-EVs enhanced NPC proliferation and suppressed cell apoptosis and ECM degradation, which was associated with the transfer of miR-31 into NPCs. In NPCs, miR-31 bound to the 3′UTR of NFAT5 and inhibited NFAT5 expression, leading to activation of the Wnt/β-catenin pathway and thus promoting NPC proliferation and reducing cell apoptosis and ECM degradation. In addition, miR-31 in hBMSC-EVs alleviated the IDD in mouse models. Taken together, miR-31 in hBMSC-EVs can alleviate IDD by targeting NFAT5 and activating the Wnt/β-catenin pathway.